2012
DOI: 10.1902/jop.2011.110250
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Partial Protocols to Assess the Prevalence of Periodontal Outcomes and Associated Sociodemographic and Behavior Factors in Adolescents and Young Adults

Abstract: Two diagonal quadrants protocol may be effective in identifying the risk factors for the most relevant periodontal outcomes in adolescence and in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 21 publications
3
52
0
3
Order By: Relevance
“…In addition, the calibration process of examiners confers reliability to our results and complex statistical procedures have improved the external validity of our study. Another limitation for our study was found: the use of CPI index 24 has important limitations such as the underestimation of prevalence of periodontal conditions due to the use of index teeth 27,28 . However, CPI is widely used around the world, conferring comparability to our results between countries.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the calibration process of examiners confers reliability to our results and complex statistical procedures have improved the external validity of our study. Another limitation for our study was found: the use of CPI index 24 has important limitations such as the underestimation of prevalence of periodontal conditions due to the use of index teeth 27,28 . However, CPI is widely used around the world, conferring comparability to our results between countries.…”
Section: Discussionmentioning
confidence: 95%
“…Naquele estudo, observou-se que a prevalência de sangramento gengival, segundo o Índice CPI, foi 28,1% (95% IC 24,8-31,5). A prevalência de cálculo dentário foi 86,1% (95% IC, 83,4-88,5) 18 . Um levantamento epidemiológico realizado na Hungria, na faixa etária de 20 a 34 anos indicou como condição periodontal predominante presença de cálculo dentário (51,1%), seguido de bolsas rasas (21,9%), o que mostra que os padrões de higiene bucal e as condições de saúde periodontal precisam ser melhorados naquele país 19 .…”
Section: Discussionunclassified
“…The use of partial examination protocols in oral health epidemiological surveys is commonly adopted in periodontal outcomes studies 16,18,19,20,21 mainly because it reduces the time and labor cost and decreases patient discomfort and examiners' fatigue 17,18 . The present study found good results regarding PP's accuracy, not only to assess prevalence, but also to assess factors associated with dental caries.…”
Section: Discussionmentioning
confidence: 99%